Evolutionary graph mining in suspicious transaction detection - Michalak, Krzysztof; Korczak, Jerzy (Ewolucyjne drążenie grafów w wykrywaniu podejrzanych transakcji, 2011)
Money laundering may involve complex organizational schemes designed to obfuscate the real purpose of money transfers. In this paper, we present a graph mining method that allows detection of transaction subgraphs containing suspicious transactions. Suspicious subgraph model is parameterized using fuzzy numbers which represent parameters of transactions and some structural features of the transaction subgraphs itself. The method presented inthis paper uses fuzzy matching of graph structures which allows detecting money-laundering schemes which differ to some extent from those annotated by an expert
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 120-129
Keywords: graph mining; evolutionary algorithms; money laundering; drążenie grafów; algorytmy ewolucyjne; pranie pieniędzy